Safety and efficacy of glofitamab for relapsed/refractory large B-cell lymphoma in a multinational real-world study - Evgenii Shumilov; Rebecca Wurm-Kuczera; Andrea Kerkhoff; Meng Wang; Thomas Melchardt; Udo Holtick; Ulrike Bacher; Philipp Staber; Paolo Mazzeo; Corinna Leng; David Böckle; Alexander Hölscher; et al. (Blood Advances)
Abstract: Glofitamab, a bispecific antibody targeting CD20 and CD3, is approved for relapsed/refractory diffuse large B-cell lymphoma (r/r DLBCL) after at least 2 prior treatment lines, but real-world data are scarce. In this retrospective, multicenter, multinational study, we evaluated the outcomes of 70 patients with r/r DLBCL treated with glofitamab as part of the compassionate use patient program in Germany, Austria, and Switzerland. The median number of prior treatment lines was 4, with 71% of patients refractory to their last treatment. Cytokine release syndrome was observed in 40% of patients (grade 3-4 in 2%), immune effector cell–associated neurotoxicity syndrome in 10% (grade 3 in 1%), and infections in 31% (grade 5 in 3%). The overall response rate was 46%, with 27% achieving complete responses (CR) and 19% partial responses. The median progression-free survival (PFS) was 3.6 months, whereas the median overall survival was 5.7 months. Notably, 13 patients (19%) were in CR 6 months after initiating glofitamab and exhibited durable responses. Elevated lactate dehydrogenase is the most robust predictor of inferior outcome. Patients pretreated with bendamustine within 6 months prior to glofitamab initiation exhibited significantly reduced PFS, suggesting that bendamustine may impair T-cell fitness and hence glofitamab efficacy. In summary, glofitamab demonstrates promising efficacy and a manageable safety profile in heavily pretreated patients with r/r DLBCL in a real-world scenario and the optimal sequence of treatments should use T-cell–depleting agents before glofitamab with caution.